Strategi Digital Marketing dalam Meningkatkan Brand Awareness pada Grosir Olshop dengan Metode N.Vivo - Yolanda, Salsa Debi; Yusniah (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Rapid economic progress has made entrepreneurs take various steps to advance their business. The methods they use always follow current trends and follow technological developments. The way people shop has changed as a result of advances in technology and easier internet access; Digital marketing methods are very important for business expansion. In this competitive business environment, the city of Medan is no less competitive in introducing local brands that they produce through digital media. One of the local brand companies in the city of Medan is Wholesaler Olshop and here the researchers want to explore what digital marketing strategies are used to increase brand awareness so that they can compete with the many fashion companies in Indonesia ranging from local brands to foreign brands. The research method used by researchers is descriptive qualitative with a case study approach to determine digital marketing strategies in increasing Brand Awareness in online wholesale companies. Descriptive is a problem formulation that describes or explores the social conditions that will be researched in a comprehensive and in-depth manner. Digital marketing strategies have become the main key in increasing brand awareness for online wholesalers. By utilizing social media such as Instagram, WhatsApp, and e-commerce platforms such as Shopee, online wholesalers can expand their audience reach and build a strong online presence.